2014
DOI: 10.1016/j.cell.2014.04.030
|View full text |Cite
|
Sign up to set email alerts
|

The HP1 Homolog Rhino Anchors a Nuclear Complex that Suppresses piRNA Precursor Splicing

Abstract: Summary piRNAs guide an adaptive genome defense system that silences transposons during germline development. The Drosophila HP1 homolog Rhino is required for germline piRNA production. We show that Rhino binds specifically to the heterochromatic clusters that produce piRNA precursors, and that binding directly correlates with piRNA production. Rhino co-localizes to germline nuclear foci with Rai1/DXO related protein Cuff and the DEAD box protein UAP56, which are also required for germline piRNA production. RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
341
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(361 citation statements)
references
References 51 publications
14
341
1
5
Order By: Relevance
“…Our recent study, along with a report by Mohn et al [4], suggests that Rhi uniquely marks the regions for piRNA production [3]. In the present study, we provide the structural evidence that Rhi binds with histone H3K9me3 through its CD in a dimerization-dependent manner.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Our recent study, along with a report by Mohn et al [4], suggests that Rhi uniquely marks the regions for piRNA production [3]. In the present study, we provide the structural evidence that Rhi binds with histone H3K9me3 through its CD in a dimerization-dependent manner.…”
supporting
confidence: 76%
“…However, how piRNA clusters are defined in the genome remains elusive. Recent studies have shown that a Heterochromatin Protein 1 (HP1) homolog Rhino (Rhi), also known as HP1D, is anchored at the dual-strand piRNA clusters to trigger the piRNA production [3,4]. Rhi is a germline-specific protein that is under rapid and positive selection during evolution [5].…”
mentioning
confidence: 99%
“…Very recently, it was determined that Rhino (an HP1a homolog) recognizes piRNA clusters through chromatin interactions. In addition, nuclear Piwi mediates Rhino localization to cluster transcripts [54,55]. Rhino, in turn, interacts indirectly with Cutoff through the protein Deadlock.…”
mentioning
confidence: 99%
“…This is reminiscent of transcriptional gene silencing in S. pombe, with dual recognition of loci by Ago1 and chromodomain protein Chp1 in the RNA-induced transcriptional silencing (RITS) complex [56]. Ultimately, the current model proposes that Cutoff protects cluster transcripts from transcriptionally-coupled pre-mRNA processing (such as polyA-tailing and splicing) [54,55] consequently favoring these transcripts to undergo piRNA rather than mRNA processing.Two additional primary processing factors are known: Trimmer and HEN1. After parsing and 5′ end formation, immature piRNAs that require 3′ end processing are loaded into Piwi.…”
mentioning
confidence: 99%
“…But in fruit-fly piRNA clusters, H3K9me3 is bound by an HP1 variant called Rhino [7][8][9][10] . Unlike HP1, Rhino assembles a protein complex that promotes transcription of piRNA clusters [11][12][13][14] .…”
mentioning
confidence: 99%